2006
DOI: 10.3354/meps309247
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of cod Gadus morhua to resuspended sediment: an experimental study of the impact of bottom trawling

Abstract: Bottom trawling activities resuspend large amounts of sediment and may be the main agent of sediment transportation in some areas. During periods of intensive fishing by large trawler fleets the high-turbidity environmental conditions they create may become semi-permanent. Little is known about the potential effects of this resuspended sediment on the survival and physiology of marine fish. We carried out a worst-case-scenario simulation whereby groups of cod Gadus morhua were exposed to the highest reported m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…an increase-rather than a decrease-in oxygen diffusion distances (e.g. [28,30,80]). For example, an increase in oxygen diffusion distances was observed in a previous study on settlement-stage A. percula exposed to the same sediment type, exposure duration and concentration (yet at an earlier developmental stage) as used in the present study [26].…”
Section: Discussionmentioning
confidence: 99%
“…an increase-rather than a decrease-in oxygen diffusion distances (e.g. [28,30,80]). For example, an increase in oxygen diffusion distances was observed in a previous study on settlement-stage A. percula exposed to the same sediment type, exposure duration and concentration (yet at an earlier developmental stage) as used in the present study [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is unlikely that changes in activity with turbidity were the result of an avoidance response to the turbidity media. Very high levels of turbidity and long exposures are required for a physiological response by cod (550 mg l K1 of suspended sediment for five days, Humborstad et al 2006) and other fish species (Servizi & Martens 1992; see also review by Newcombe & McDonald 1991). Similar responses in our experiments were unlikely as the concentration of turbidity media was low (less than 47 mg l K1 ) and exposure times were short (less than 2.5 h).…”
Section: Discussionmentioning
confidence: 99%
“…In cases where streams are aggraded in patchy distributions, fish can often avoid higher sediment concentrations (Sullivan and Watzin 2010), but if the spatial distribution of suspended sediments is more uniform, then adverse effects via habitat alterations may be spread across multiple life stages (e.g., adults, nest building, egg development, and fry feeding) (Newcombe and Jensen 1996;Galbraith et al 2006). Several studies have found that exposure of fish to suspended solids can elicit a primary stress responses (PSR) by increasing both circulating and whole blood cortisol concentrations and levels, respectively (Redding et al 1987;Humborstad et al 2006;Sutherland et al 2008; Rich 2010). There are fewer studies on the secondary stress responses (SSR) in fish exposed to SS and turbidity due to dredging, although three laboratory-based studies were reported in Rich (2010).…”
Section: Stressor Duration Tolerance and Lethalitymentioning
confidence: 99%